Randomized trial studying metabolic outcomes and quality of life after adrenalectomy versus conservative management for mild autonomous cortisol secretion - Ueland, Grethe; Ragnarsson, Oskar; Heie, Anette; Kjellbom, Albin ; 0000-0002-4886-4807; Lindgren, Ola; Muth, Andreas; Palazzo, Fausto; Poulsen, Per L.; Rolighed, Lars; Thordarson, Hrafnkell Baldur; Wernig, Florian; Bergenfelz, Anders (Endocrine Connections, 2025)
Objective: Evaluate the impact of adrenalectomy on metabolic parameters and quality of life (QoL) in patients with mild autonomous cortisol secretion (MACS). Method: A multicenter prospective randomized clinical trial compared adrenalectomy with conservative management. Metabolic parameters and QoL were assessed at baseline and after 2 years. Results: Forty-three MACS patients with a single adrenal adenoma were randomized to either adrenalectomy (n =21) or conservative management (n = 22). At baseline, 33 patients had hypertension, 13 had type 2 diabetes (T2D), 18 used statins, and nine patients had osteoporosis. After 2 years, normalization of cortisol levels post 1 mg dexamethasone suppression test was achieved in 19/21 adrenalectomy patients compared to 2/22 patients in the conservative group (P < 0.01). All adrenalectomy patients had a significant increase in ACTH and DHEA-S. Office blood pressure and daily defined doses of antihypertensives (DDD) improved in nine of 12 adrenalectomy patients versus four of 15 conservatively treated patients (P = 0.01). Using 24 h blood pressure and DDD, improvement rates were five of 11 in the adrenalectomy group and six of 15 in the conservative group (P = 0.78). Among patients without T2D, the 120 min glucose level during oral glucose tolerance test was lower in the adrenalectomy group (6.2 vs 7.3 mmol/L, P = 0.04), but within-group changes were not different (P = 0.76). There were no statistically significant differences in QoL between the two groups. Conclusion: Adrenalectomy showed trends toward improvement in office blood pressure and glucose metabolism in MACS, suggesting possible reduction in cardiovascular risk and metabolic complications. Clinical trials number: NCT01246739.
Publisher Copyright: © 2025 the author(s).
Keywords: adrenal incidentalomas; adrenalectomy; MACS; metabolic consequences; mild autonomous cortisol secretion